2012
DOI: 10.1007/s00266-012-9972-4
|View full text |Cite
|
Sign up to set email alerts
|

Running Circular Suture Technique for Reduction Mammaplasty and Mastopexy

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Quan et al [6] reported that pseudoptosis develops most commonly and most rapidly in the first postoperative year and that bottoming out progresses significantly, but mildly, during the following 2 years. Efforts to achieve a sustainable breast mould that will not deform significantly over the long-term have yielded the development of various methods and modifications JOURNAL OF PLASTIC SURGERY AND HAND SURGERY 5 [7][8][9][10][11][12][13][14]. The inferior pedicle technique, which was first introduced four decades ago, remains the most popular technique because of its preservation of sensation and vascularisation of the nipple, especially in patients with a long sternal notch-to-nipple distance [4].…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al [6] reported that pseudoptosis develops most commonly and most rapidly in the first postoperative year and that bottoming out progresses significantly, but mildly, during the following 2 years. Efforts to achieve a sustainable breast mould that will not deform significantly over the long-term have yielded the development of various methods and modifications JOURNAL OF PLASTIC SURGERY AND HAND SURGERY 5 [7][8][9][10][11][12][13][14]. The inferior pedicle technique, which was first introduced four decades ago, remains the most popular technique because of its preservation of sensation and vascularisation of the nipple, especially in patients with a long sternal notch-to-nipple distance [4].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous circular suturing technique: Incisions are previously marked and are based on points A, B, C, and D, as established by Pitanguy; however, this sequential marking was advocated by Bueno et al 12 , as described below.…”
Section: Preoperative Marking and Surgical Techniquementioning
confidence: 99%
“…The use of purse-string circular suturing or continuous circular suturing of the breast was described in 2003; this involved the aponeurosis of the pectoralis major muscle, to reduce the mammary base and project the nipple-areola complex (NAC) at the vortex of the mammary cone, with restoration of the superior pole, and without the use of flaps 12,13 .…”
Section: Introductionmentioning
confidence: 99%